Saccharide Detection Based on the Amplified Fluorescence Quenching of a Water-Soluble Poly(phenylene ethynylene) by a Boronic Acid Functionalized Benzyl Viologen Derivative - DiCesare, Nicolas (Langmuir : the ACS journal of surfaces and colloids, 2002)
The amplified quenching of an anionic conjugated polymer, sulfonated poly(phenylene ethynylene) (PPE-SO3 -), by a cationic quencher comprising a boronic acid functionalized benzyl viologen (p-BV2+), has been used to optically detect sugars. In the absence of sugar, a strong polymer/quencher interaction leads to superlinear quenching. In the presence of sugar at pH 7.4, the dicationic viologen derivative forms a neutral zwitterionic species, reducing its ability to complex with and quench the anionic polymer's emission. Addition of sugar to the polymer/quencher system leads a large increase in the fluorescence intensity (up to 70-fold in one case). Spectral data, quenching parameters, and sugar titration curves are presented and discussed in terms of future development of glucose sensors